2005
DOI: 10.1158/0008-5472.can-04-3954
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde-3-Phosphate Dehydrogenase Binds to the AU-Rich 3′ Untranslated Region of Colony-Stimulating Factor–1 (CSF-1) Messenger RNA in Human Ovarian Cancer Cells: Possible Role in CSF-1 Posttranscriptional Regulation and Tumor Phenotype

Abstract: The overexpression of the colony-stimulating factor-1(CSF-1) by epithelial ovarian cancer cells enhances invasiveness and metastatic properties, contributing to the poor prognosis of the patients. It has been suggested that CSF-1 3Vuntranslated region containing AU-rich elements (ARE) could regulate CSF-1 posttranscriptional expression and be responsible for its aberrant abundance in such cancer cells. In this study, normal (NOSE.1) and malignant (Hey) ovarian epithelial cells were used to examine CSF-1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 41 publications
5
106
0
Order By: Relevance
“…24), we examined whether an interaction between GAPDH and the telomerase RNA moiety hTERC exists. As a positive control for GAPDH RNA binding, an AU-rich RNA molecule (4× AUUUA) was used, as has been previously demonstrated to interact with GAPDH (26). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24), we examined whether an interaction between GAPDH and the telomerase RNA moiety hTERC exists. As a positive control for GAPDH RNA binding, an AU-rich RNA molecule (4× AUUUA) was used, as has been previously demonstrated to interact with GAPDH (26). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the nucleus, GAPDH is the key component of a gene transcriptosome for cell division (6). Binding to nucleic acids, GAPDH is implicated in mediating RNA nuclear export (22), protecting mRNA from degradation through interaction with AU-rich elements (AREs) (26) and the repair of DNA (27). Moreover, studies have shown that GAPDH binds to telomeres directly (8,9).…”
mentioning
confidence: 99%
“…Interestingly, the only pathway that was overrepresented by genes whose translation was decreased after irradiation was monosaccharide catabolism, specifically glycolysis. Whereas GAPDH is a glycolytic enzyme and yet was increased in the polysome fraction after irradiation, recent reports indicate that it has additional activities, including RNA binding (23).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, high carbohydrates, through the up-regulation of a series of glycolysis-related genes, may subsequently activate the glycolytic pathway and is closely related to the tumorigenesis of CRC. GAPD is overexpressed in both ovarian and prostate cancers, and is proved to be crucial in metastatic properties (31)(32)(33). In addition, GAPD is associated with the proliferation and aggressiveness of breast cancer cells (34).…”
Section: Discussionmentioning
confidence: 99%